Selected problems in physical chemistry : strategies and interpretations - Ilich, Predrag-Peter. (New York : Springer, 2010)
"This book is a collection of 50 original problems in physical chemistry including several living systems. Each problem is accompanied by a detailed step-by-step solution, organized as strategy, assumptions, approximations, numerical calculation and interpretation. Solutions to the key problems (e.g. thermal equilibration, ligand-receptor interaction, aminoacid zwitterions, HOMO-LUMO gap) are accompanied by simple introductory explanations. In addition, informal notes are provided on difficult concepts, for example: entropy, reaction activation barrier, wave mechanics. Schemes, diagrams and structural formulas accompany most solutions and explanations. Thus, this textbook may serve as a self-tutorial for undergraduate students in physical chemistry, biophysics, biochemistry, and medicinal chemistry."--Pub. desc.
Includes bibliographical references and index.
Keywords: Chemistry, Physical and theoretical -- Problems, exercises, etc